DIAGNOSIS OF POWER OIL IN PUMPING UNITS COOLING SYSTEMS OF POWER PLANT EQUIPMENT - ZAITSEV, SERGEY; ТIKHENKO, VALENTIN (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article presents the results of improving the methods for diagnosing the energy oil "Tp-30" of the pumping unit of the NPP equipment coolant circulation system. When studying the physicochemical and thermophysical properties of this oil, it was found that: the indicators "acid number", "water content", "content of mechanical impurities", "content of the additive "Ionol", "flash point", "kinematic viscosity" correspond to the established standards. When determining the concentration of the additive "Ionol" in the sample of this oil: the method of adding the additive "Ionol" is used; in the obtained calculation formula, the values of the distribution coefficient for the additive "Ionol" in the system "turbine oil – additive "Ionol" – liquid extractant" are not used, which simplifies the study of the content of this additive in turbine oil. The water content in mineral turbine oil, determined by gas chromatography and coulometric titration with K. Fischer's reagent, exceeds the water content in this oil, determined by thermal extraction. When studying the effect of liquid extraction temperature on additives "Ionol" (when determining its content in a given oil), it was found by gas chromatography that: the dependence of the distribution coefficients Ki on temperature t in the temperature range 15–75 0С can be expressed by the equation lnKi = А/(t+273) - B ; It is recommended to extract the Ionol additive from this oil at a temperature of (20 ± 2) °С or at a temperature of (65 ± 10)  °С. When studying the effect of the chemical nature of the extractant on the ability to extract the "Ionol" additive from this oil, it was found that: ethanol, isopropanol, acetonitrile can be used as extractants of the "Ionol" additive, and the mixture "acetonitrile – water" cannot be recommended as such extractant. The results obtained can be used to improve the method of diagnosing mineral turbine oil "Tp-30" of the pumping unit of the coolant circulation system of the equipment of the second circuit of NPP with a pressurized water power reactor.
Keywords: mineral oil; physical and chemical properties; antioxidant additive; extractant